EFFECT OF MOTIVATION AND SKILLS ON THE PERFORMANCE OF EMPLOYEES ON PDAM TIRTA KAMPAR REGENCY - Budi Hidayat; Suarni Norawati; Muhammad Salis (STIE Bangkinang Publishing, 2020)
This study aims to determine the effect of work motivation and skills on employee performance at PDAM Tirta Kampar. The population in this study were all employees at PDAM Tirta Kampar. The sample was conducted using the census method of 102 employees. The data collection techniques used were questionnaires and research files. The data analysis technique used is multiple linear regression analysis with a significant level (α) of 0.05. Data analysis was performed using multiple linear regression models. Based on the partial test, the work motivation variable is more dominant in influencing the employee performance at PDAM Tirta Kampar. Based on the research results, it can be concluded that work motivation and skills have an effect on employee performance at PDAM Tirta Kampar. The contribution of the independent variable to the dependent variable is 65.6%, while the remaining 34.4% is influenced by other variables not examined in this study.